A Three-Dimensional Framework of Character Education in Senior High Schools: A Systematic Literature Review - Dian Sartika; Siti Zulaikha; Linda Ika Mayasari (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to develop a conceptual framework for character education in senior high schools by systematically mapping implementation patterns, challenges, and strategies to strengthen character values. The research employed a conceptual design using a Systematic Literature Review approach. The units of analysis were research articles on character education at the senior high school level published between 2015 and 2024, sourced from reputable national and international journals. Through predefined inclusion and exclusion criteria, 37 articles were selected for analysis. Data were examined using content analysis and thematic coding to identify recurring patterns, conceptual relationships, and dominant themes. The findings reveal that character education is constructed through the integration of three core dimensions. The pedagogical dimension emphasizes reflective and experiential learning, positioning students as moral subjects. The cultural dimension is reflected in consistent school culture, educator role modeling, and supportive social interactions. The structural dimension ensures sustainability through moral leadership, participatory policies, and partnerships with families and communities; however, weak integration reduces overall effectiveness.